Evaluación de dos tipos de sistemas de producción (piso y jaula) de pollos Broiler, en el sector de San Cayetano bajo, parroquia el valle, cantón Loja - Coronel Jaramillo, Jose Andres (2014)
The study evaluation of two types of systems (Floor And Cage) of broiler chickens, in the neighborhood San Cayetano Bajo, El Valle parish in Loja, the method tables of averages was used as the variables they evaluated were: consumption of food, the same as he did daily and is expressed in g/animal. Further increase in weight, where the weight was taken animals to establish their weekly weight change in each week and ultimately profitability, which was determined with a staff cost of production and sale of animals, which we established profitability. Regarding the management of the experiment began with the manufacture of cages and pens to the floor, which were located in the same closed environment before the experiment which were cleansed, disinfected and identified according to the treatment. The animals were dewormed and maintained in two groups of sixty chickens to the floor by the time a week to get their adaptation to the environment. Once adapted spent the second week of their experimental lodging that is sixty chickens to the floor pens and sixty chickens cage system. In each group three repetitions of twenty animals each were performed. Animals from the first to fifth week were fed commercial feeds and from the sixth to eighth mixed diet consisting of 80% and 20% balanced corn. The conclusions get the this study were: The less feed intake is in the T2 system in Cage with 11,46 g compared to higher consumption obtained in the system T1 rearing system on the floor scored 12,59 g. The high increase in the average weight gained aging treatment up to 406 grams floor unlike the two treatment cage was 387 g. The best feed conversion obtained treating the T2 system with 2.37 than cage rearing system T1 which scored 2.47 on the floor. Food with mixed platter, balanced by 80% more yellow corn, feed conversion delays and demonstrated in the consumption of the eighth week where it grows in feed conversion t2 cage system to 5.25 and the t 1 system in flat to 4.94. The more profitable the treatment obtained in two cages system with a 29.87% compared to the performance of two treatment system to the floor which gave 28.76%. The highest mortality occurred in the first treatment with a 6.3% than 1.6% which was presented in the second treatment cage system, giving an overall average of 5%.